Soil Exploration in Selected Evacuation Center - Marites M. Bardelas; Vicente D. Carillo Jr. (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Tanauan Leyte being one of the hardly hit areas during the devastation of typhoon HAIYAN, has been given opportunities of different rehabilitation projects to recover and furthermore give priority to disaster risk reduction and management. One of those projects was to build designated Evacuation Centers on different priority areas in typhoon stricken-communities. Wherefore, a further study was done to areas concern to build better Evacuation Centers. The following barangays identified are located along coastal area of Tanauan classified as the most vulnerable in terms of typhoon, surges and other natural calamities. Manpower was hired to help in conducting the soil exploration and utilized appropriate equipment, apparatuses for soil mechanic analysis. Soil samples were systematically gathered using auger boring method and soil penetration test for three to six meters depth using a split barrel, labeled and placed in marked containers. Soil Penetration Test was conducted to determine the soil bearing capacity as basis on the design of building and further recommend for a resilient structure. The water content and liquid limit determination is determined for a possible liquefaction. The results show the different soil classification, soil bearing capacity and liquid susceptibility among five barangays under investigation. The findings suggests that the proposed location of the four barangays are capable of bearing a two-storey structure except for one barangay provided that the structure will conform to the national building code for an evacuation center. Keywords: Evacuation center, Soil exploration, Soil mechanics, Soil samples, Auger boring, Soil bearing capacity, Liquefaction, Site investigation, Haiyan typhoon, Disaster